Barriers in the energy of deformed nuclei - V. Yu. Denisov; T. O. Margitych (Ядерна фізика та енергетика)
Interaction energy between two nuclei considering to their deformations is studied. Coulomb and nuclear in-teraction energies, as well as the deformation energies of both nuclei, are taken into account at evaluation of the interaction energy. It is shown that the barrier related to the interaction energy of two nuclei depends on the de-formations and the height of the minimal barrier is evaluated. It is obtained that the heavier nucleus-nucleus sys-tems have large deformation values at the lowest barrier. The difference between the barrier between spherical nuclei and the lowest barrier between deformed nuclei increases with the mass and the charge of the interacting nuclei.